ORCHIDACEAE PULAU RUBIAH KOTA MADYA SABANG PROVINSI ACEH - Djufri; Hasanuddin; Fauzi (Biotik, 2015)
This study aims to know types of orchid (Orchidaceae) on Rubiah Island of Sabang City. Data were collected by using exploration method (observation). The entire island was explored by following the existing tracks or roads. The study was conducted in two (2) locations, on the outskirts of the island ( 0 s / d 100 m from the seashore ) and the central region of the island (100 m to 500 m from the seashore). The data were analyzed descriptively and displayed in the form of figures and tables. From the results of the research, it was found that there were 11 kinds of orchids which consists of six genera, they are: Aerides, Coelogyne, Cymbidium, Dendrobium, Phalaenopsis, and Vanda. The orchid species found in all of the observation point is asperata Coelogyne, Dendrobium phalaenopsis and Vanda limbata.